Hearing Assessment after Treatment of Nasopharyngeal Carcinoma with CRT and IMRT Techniques. (16th August 2015) - Hwang, Chung-Feng; Fang, Fu-Min; Zhuo, Ming-Ying; Yang, Chao-Hui; Yang, Li-Na; Hsieh, Hui-Shan
Abstract : Objectives . This study analyzed the long-term hearing loss after treatment of primary nasopharyngeal carcinoma to elucidate its causal factors. Methods . Ninety-two nasopharyngeal carcinoma patients were treated with radiotherapy or chemoradiotherapy. Pure tone audiometry was performed before the therapy and annually up to 9 years after completing treatment. The hearing thresholds were corrected for age-related deterioration and compared to the results without adjusting for age. Results . The mean air and bone conduction threshold with and without correction for age-related deterioration differed significantly 2–9 years after completing radiotherapyp < 0.05 . The audiometry results with age correction showed a flattened configuration compared to the results without age correction. The total radiation dose and radiation modality showed a causal relationship with a greater incidence of hearing loss after therapyp < 0.05 . There was more deterioration in the air and bone hearing thresholds with conformal radiotherapy than intensity-modulated radiotherapyp < 0.001 . A radiation dose >72 cGy resulted in more severe hearing loss than <72 cGyp < 0.05 . Conclusion . Hearing loss after completing therapy should be corrected for age-related hearing deterioration to reveal the true extent to which the loss is a therapeutic complication. Both the radiation modality used and the dose were significantly associated with hearing loss.